SOLUTIONS FOR LINEAR FREDHOLM-VOLTTERRA INTEGRAL EQUATIONS OF THE SECOND KIND USING THE REPEATED CORRECTED TRAPEZOIDAL AND SIMPSON’S METHODS - Majeed, Salam J; Omran, Huda H (Al-Nahrain Journal of Science, 2010)
In this paper we introduce numerical methods for solving linear Fredholm–Volterra integralequations of the second kind. The main idea is based on the corrected trapezoidal and Simpson’s1/3 quadrature formulas. These techniques are very effective. Numerical results are illustrated by different examples